2009
DOI: 10.1088/0029-5515/49/6/065028
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic modelling of impurity transport in detached plasma for integrated divertor simulation with SONIC (SOLDOR/NEUT2D/IMPMC/EDDY)

Abstract: An integrated divertor simulation code SONIC has been developed. The self-consistent coupling of an MC impurity code IMPMC to a divertor code SOLDOR/NEUT2D is succeeded by overcoming the intrinsic problems of Monte Carlo (MC) modelling for impurity transport. MC modelling for impurity transport is required in order to take into account the kinetic effect and the complex dissociation processes of hydrocarbons. The integrated divertor code SONIC enables us to investigate the details of impurity transport includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
63
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 72 publications
(63 citation statements)
references
References 20 publications
0
63
0
Order By: Relevance
“…A suite of integrated divertor codes SONIC [9,10] is applied to the physics design study of the DEMO divertor plasma. The SONIC suite consists of the 2-D plasma fluid code (SOLDOR), the neutral Monte-Carlo kinetic code (NEUT2D) and the impurity Monte-Carlo kinetic code (IMPMC).…”
Section: Numerical Modelmentioning
confidence: 99%
“…A suite of integrated divertor codes SONIC [9,10] is applied to the physics design study of the DEMO divertor plasma. The SONIC suite consists of the 2-D plasma fluid code (SOLDOR), the neutral Monte-Carlo kinetic code (NEUT2D) and the impurity Monte-Carlo kinetic code (IMPMC).…”
Section: Numerical Modelmentioning
confidence: 99%
“…In JAEA, a suite of integrated divertor codes SONIC [8,9] has been developed for the interpretation and prediction of the divertor plasma characteristics. The SONIC suite consists of the 2D plasma fluid code (SOLDOR), the neutral Monte-Carlo (MC) code (NEUT2D) and the impurity MC code (IMPMC).…”
Section: Integrated Divertor Code Sonicmentioning
confidence: 99%
“…On the other hand, disadvantages of the MC approach are large Monte-Carlo noise, large computer resource etc. Recently, these disadvantages have been overcome, and the IMPMC code has been self-consistently integrated with SOLDOR/NEUT2D [9]. In the present version of the SONIC, only one impurity species can be treated by IMPMC.…”
Section: Integrated Divertor Code Sonicmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, a particle code PARASOL [35] is used to develop kinetic models introduced into SOLDOR and a 3D MC plasma-wallinteraction code EDDY [36] is integrated with SONIC for the self-consistent calculation of physical/chemical sputtering, complex dissociation processes and energy/species dependent reflection. The dynamic evolution of X-point MARFE observed in JT-60U was investigated with SONIC code [37]. It was found that the hydrocarbons sputtered from the dome contribute to the enhanced radiation near the X-point.…”
Section: Coupling Between Core and Sol/divertor Integrated Modelsmentioning
confidence: 99%